1970
DOI: 10.1029/ja075i025p04699
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent loss of ring current protons

Abstract: Ring current protons (<50 kev), which are unaffected by ion cyclotron waves outside the plasmapause, undergo strong turbulent diffusion just inside the plasmapause. Lifetimes from ion cyclotron turbulence are predicted to be of the order of 1 hour, as observed by Frank for 3≤L≤5. During the main phase of a geomagnetic storm, the protons rapidly diffuse across the plasmapause (probably at the Bohm rate) and are lost before reaching the noon meridian, thus giving rise to the asymmetric part of the ring current. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
376
1

Year Published

1975
1975
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(409 citation statements)
references
References 31 publications
22
376
1
Order By: Relevance
“…Whether ion cyclotron resonance interactions contribute significantly to this initial rapid decay, as theoreticai work on this inechanism has suggested, (Cornwall, et al, 1970) has not as yet been demonstrated, although some observations of ion cyclotron waves measured by Explorer 45 during magnetic storms have been reported QT ylor, , et al, 1975). !n the second slower decay phase, as we have shown in this pager, charge exchange appears as the dominant decay mechanism for the nearequatorially mirroring protons.…”
Section: Decay Mechanismmentioning
confidence: 99%
“…Whether ion cyclotron resonance interactions contribute significantly to this initial rapid decay, as theoreticai work on this inechanism has suggested, (Cornwall, et al, 1970) has not as yet been demonstrated, although some observations of ion cyclotron waves measured by Explorer 45 during magnetic storms have been reported QT ylor, , et al, 1975). !n the second slower decay phase, as we have shown in this pager, charge exchange appears as the dominant decay mechanism for the nearequatorially mirroring protons.…”
Section: Decay Mechanismmentioning
confidence: 99%
“…The equatorial mapping of the detached arc to the plasmaspheric drainage plume is suggestive of a mechanism involving the interaction of hot ring current ions with cold plasmaspheric material. This is an environment suitable for the amplification of EMIC waves as first predicted by Cornwall et al [1970] and subsequently investigated by many others [e.g., Anderson et al, 1992;Gary et al, 1995]. Scattering by EMIC waves will lead to the precipitation of ring current protons and the excitation of subauroral arcs Spasojevic et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…E-t spectrograms of electron and proton intensities encountered for a 48-hour period are presented in Figure 16. The pitch angles sampled in this and plasma sheet and thus also in their precipitation into the auroral zone [Cornwall et al, 1970]. …”
Section: The Magnetospheric Plasmasmentioning
confidence: 99%